Carbonic anhydrase inhibitors limit complications in X-linked retinoschisis - Wey, Stephanie; Brill, Daniel A.; Miraldi Utz, Virginia; Sisk, Robert A. (Frontiers in Medicine, 2023)
Purpose: Carbonic anhydrase inhibitors (CAIs) reduce macular schisis in patients with X-linked retinoschisis (XLRS). The purpose of this study was to determine if CAIs reduce the incidence of complications from XLRS, including macular atrophy, retinal tears, and retinal detachment (RD), the most common causes of vision loss in patients with XLRS.: For this retrospective interventional case series, a chart review of patients examined at Cincinnati Children's Medical Center [CCHMC] and Cincinnati Eye Institute [CEI] between 1/1/2015 and 1/16/2023 was performed. Male patients were included based on genetically-confirmed RS1 or typical clinical presentation with known family history of XLRS with at least two follow-up visits. Results: 28 patients (56 eyes) with XLRS were included. There were 10 RS1 variants among the 21 genotyped patients. Median age at clinical diagnosis was 10.4 years old (range: 0.4 to 55.7 years) with median follow-up time of 4.7 years (range: 0.2 to 38.3 years). Median presenting Snellen visual acuity was 20/60 (logMAR 0.48, range: 0.18 to 3). In 26 eyes of 15 patients treated with CAIs, median CST pre-treatment was 416 microns (range: 198 to 701 microns), and median percentage decrease in CST on treatment was 21.8% (range: 0% to 74.5%) from highest pre-treatment CST.Reduction in CST with CAI use was statistically significant (p=0.02), but not logMAR VA (p=0.64).There was no significant difference in CST between patients treated with topical versus oral CAI (p=0.95) or between patients with partial or complete CAI adherence (p=0.60). 10 eyes of 7 patients had an RD requiring surgical intervention. No treated eyes developed new macular atrophy, peripheral retinoschisis, retinal tears, or RD; two eyes on topical CAIs had spontaneous resolution of bullous peripheral retinoschisis.During the follow-up period, patients taking CAIs reduced macular schisis and did not experience new complications of macular atrophy, retinal tears, or RD. This is a relatively large